Strict Liability of Shipping Corporations on Unseaworthy Ships - Husein Layn; Elsa R. M. Toule; D. J. A. Hehanussa (Journal of World Science, 2026)
Shipping safety is a fundamental aspect of connectivity in the Maluku archipelago. However, the high rate of maritime accidents caused by unseaworthiness factors such as overloading and the absence of safety equipment indicates weaknesses in the current legal liability system, which tends to focus solely on individual shipmasters (captains). This study aims to analyze the urgency and mechanism of applying the principle of strict liability to shipping corporations that operate unseaworthy vessels within the working area of the Class I Port Authority and Office (KSOP) Ambon. The research method employed was normative juridical, utilizing statutory and conceptual approaches. The results indicate that operating an unseaworthy vessel is a type of regulatory offense that carries significant risks to public safety, therefore, the requirement to prove criminal intent (mens rea), which is often difficult to establish within corporate structures, can be waived. Under the strict liability principle, corporations can be held criminally liable based on objective evidence of violating seaworthiness standards (actus reus). Geographic challenges in Maluku, where only 24 out of 75 ports have permanent officers, reinforce the need for a firm legal doctrine to create a deterrent effect for shipowners. This study concludes that the explicit application of strict liability in maritime regulations will encourage corporations to systemically improve safety standards and ensure legal certainty for the public utilizing sea transportation services.